2009
DOI: 10.1142/s1758825109000137
|View full text |Cite
|
Sign up to set email alerts
|

Lateral and Torsional Vibrations of a Two-Disk Rotor-Stator System With Axial Contact/Rubs

Abstract: The dynamics of a rotor system with axial contact/rub events between the disks and stator are investigated by numerical simulations. The formula for determining the contact/rub points, axial contact forces and dry friction forces are deduced. To account for their influence, the axial contact forces are substituted by equivalent forces acting at the disk centers, based on the equivalent moment rule. One-parametric model is used to estimate the contact-induced dry friction forces. The coupled equations of latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…His research shows that the axial rub results in complicated behaviors, such as quasi-periodical or chaotic responses, and the rotordyanmics are similar to the radial rub impact. Kunpeng and Qian 23 numerically investigated the lateral–torsional coupling vibration of a rotor system influenced by axial contact/rubs between rotor disks and stator. The calculation shows that the lateral vibration changes from periodic to chaotic, and the torsional natural frequency appears as the occurrence of the axial rub.…”
Section: Introductionmentioning
confidence: 99%
“…His research shows that the axial rub results in complicated behaviors, such as quasi-periodical or chaotic responses, and the rotordyanmics are similar to the radial rub impact. Kunpeng and Qian 23 numerically investigated the lateral–torsional coupling vibration of a rotor system influenced by axial contact/rubs between rotor disks and stator. The calculation shows that the lateral vibration changes from periodic to chaotic, and the torsional natural frequency appears as the occurrence of the axial rub.…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that the nonuniform initial gap led to rich vibration phenomena in the dynamic responses, especially in the torsional responses. Zhang and Ding [22,23] investigated the influence of rubimpact on the bending and torsional vibrations of a two-disk rotor-stator system. e results indicated that the spectrum analyses of the torsional vibrations were more suitable to determine the axial contact-rubs.…”
Section: Introductionmentioning
confidence: 99%
“…Axially moving tensioned beams are common constituent elements in many mechanical systems such as magnetic tapes, robotic manipulators, textile fibers, and conveyer belts [Chen, 2005a;Hua et al, 2005;Zhang and Ding, 2009;Sandilo and van Horssen, 2012]. One important problem in these axially moving systems is the occurrence of large unwanted transverse vibrations due to the parametric and external excitations.…”
Section: Introductionmentioning
confidence: 99%